Quality assurance of oral and maxillofacial teleradiology: a literature review - Suraidah, Suraidah; Rahman, Fadhlil Ulum Abdul (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This article aims to inform dentists and dental specialists about quality assurance in oral and maxillofacial teleradiology as a communication tool between radiologists and colleagues using a teleradiology system. Review: Teleradiology is a radiological practice that allows the transmission and interpretation of diagnostic images, such as intraoral, extraoral, and CT scans, from different geographic locations. In dentistry, oral and maxillofacial radiologists often interpret these images remotely. To be effective diagnostically, teleradiology must maintain high-quality imaging standards and follow radiological care principles. Quality assurance (QA) plays a vital role in ensuring image clarity, diagnostic accuracy, and patient safety. QA involves implementing standard protocols for image acquisition and transmission using systems such as DICOM (Digital Imaging and Communication in Medicine) and PACS (Picture Archiving and Communication System), under radiologist supervision and with professional collaboration. Compression formats like JPEG and wavelet, whether lossy or lossless, must be managed properly to avoid image degradation. In clinical dental practice, teleradiology is utilized through teleconsultation, tele-consultancy, and telemanagement, relying on secure communication networks and professional interaction to protect data integrity and confidentiality. Conclusion: Teleradiology improves access to radiologic interpretation and secondary consultations while offering flexibility in image review. Images can be simultaneously accessed from multiple locations. Successful implementation requires proper compression, stable internet, patient privacy, authentication, and data integrity. With adequate QA measures, teleradiology significantly enhances diagnostic services and patient care outcomes. Keywords: Quality assurance, oral and maxillofacial, teleradiology